A modelling language and a tool for web services composition. (1st January 2014) - Bachtarzi, Fayçal; Chaoui, Allaoua
Web services technology is the most common implementation of service oriented architecture. Web services are based on open technologies such as eXtensible Markup Language (XML) and offer a distributed approach for the integration of heterogeneous applications across the internet. The process of combining web services functionalities into one composite service is called web services composition. To perform this task, several languages such as Business Process Execution Language (BPEL), Web Services Flow Language (WSFL) and Web Service Choreography Interface (WSCI) have emerged. These languages are based on programming concepts and neglect the specification step which is very important in any software development process. In this paper, we address the formal specification of web services descriptions and the modelling of their composition using the model driven engineering principles. To this end, we propose a domain specific language (DSL) called S-GNet. The proposed DSL introduces new modelling elements which make it well adapted to the web services characteristics. We also propose a graph grammar which transforms Web Services Description Language (WSDL) descriptions into their equivalent S-GNet specifications. This grammar is integrated within an S-GNet modelling tool.